Laboratory Service Process Checklist: Preventive Measures to Increase Blood Glucose Test Accuracy - Setyawan, Yudi; Wardhani, Viera (Fakultas Kedokteran Universitas Brawijaya)
The accuracy of the blood glucose test results is an important measure for hospital quality due to its effect on treatment plan, decision and outcome. This study aims to develop checklists model to improve the laboratory results accuracy. The development of the checklist was based on laboratory services process: pre-analytic, analytic, and post-analytic which further implemented for all requests for blood glucose tests during study period (65 examination) in the first week of October 2020. After the implementation, result showed no incidence of test in-accuracy when conformed with patient clinical information. Staff express that the checklist is fast and easy to complete (3-5 minutes), and beneficial. Problem occurs when the workload is high because of limited number of staff at night shift or high patient volume leading to delay in checklist completeness. Therefore, regular monitoring and evaluation was suggested to ensure compliance, in addition to dividing the checklist performed in 2 stages. The pre-analytic stage is carried out first for all patients followed by the analytical and post-analytic stages because these two activities were located in different floor. It can be concluded that the use of checklists is effective as preventive measure increase the conformity of laboratory examination results with patient clinical information.Keywords: Laboratory checklist, test accuracy, patient safety.